2016
DOI: 10.1021/acsami.6b00831
|View full text |Cite
|
Sign up to set email alerts
|

Li7La3Zr2O12 Interface Modification for Li Dendrite Prevention

Abstract: Al-contaminated Ta-substituted Li7La3Zr2O12 (LLZ:Ta), synthesized via solid-state reaction, and Al-free Ta-substituted Li7La3Zr2O12, fabricated by hot-press sintering (HP-LLZ:Ta), have relative densities of 92.7% and 99.0%, respectively. Impedance spectra show the total conductivity of LLZ:Ta to be 0.71 mS cm(-1) at 30 °C and that of HP-LLZ:Ta to be 1.18 mS cm(-1). The lower total conductivity for LLZ:Ta than HP-LLZ:Ta was attributed to the higher grain boundary resistance and lower relative density of LLZ:Ta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
637
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 694 publications
(663 citation statements)
references
References 28 publications
21
637
4
1
Order By: Relevance
“…Thin film alloy prepared by magnetron sputtering, physical vapor deposition, or chemical vapor deposition have an outstanding capacity retention, which can be attributed to the strong adhesion of atoms onto the substrate support and elimination of the changing phase structure with different Li host. [126][127][128][129][130][131][132][133][134][135][136] However, Li-Al alloy mounds were present on the Al anode film surface instead of the Al-solid electrolyte surface, [126] and the cell capacity degraded as a result of Li trapping in these alloy mounds. This result indicates that only alloy film anodes seem inadequate for the solid-state Li metal battery.…”
Section: Interface Between Anode and Solid Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Thin film alloy prepared by magnetron sputtering, physical vapor deposition, or chemical vapor deposition have an outstanding capacity retention, which can be attributed to the strong adhesion of atoms onto the substrate support and elimination of the changing phase structure with different Li host. [126][127][128][129][130][131][132][133][134][135][136] However, Li-Al alloy mounds were present on the Al anode film surface instead of the Al-solid electrolyte surface, [126] and the cell capacity degraded as a result of Li trapping in these alloy mounds. This result indicates that only alloy film anodes seem inadequate for the solid-state Li metal battery.…”
Section: Interface Between Anode and Solid Electrolytementioning
confidence: 99%
“…The constant dc measurement (Figure 16g) also has a considerably lower starting voltage for Au-coated LLZ, which can be attributed to the lower contact resistance between Li metal and solid electrolyte. [130] In addition to Si and Au, the film coating of ZnO, Ge, and Al have similar advantages. [134,136,137] Surprisingly, the surface coated with ultrathin Al 2 O 3 from atomic layer deposition (ALD) effectively negates the interfacial resistance from 1710 to 1 Ω cm 2 , as illustrated in Figure 17c and provides a stable voltage of 13 mV in Li plating and stripping plots (Figure 17d).…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…While for thin-film batteries, prepared by cost-intensive sputtering or other (vacuum) deposition techniques, Li metal anodes might be difficult to implement, for bulk-type batteries the use of metal anodes will provide the necessary jump in energy density to make them a serious option for electric vehicles. Although the ceramic acts as a 'dense' membrane the risk of unsolicited Li plating and dendrite formation along grain boundaries is still given [78].…”
Section: The Demands On Solid Electrolytes and All-solid-state Batteriesmentioning
confidence: 99%
“…Among them, the solid electrolyte-electrode interface is the bottleneck for Li transport. 11,12 The high interfacial resistance between the solid electrolyte and electrode render the charge transfer and Li transport very slow, and thus, it limits the electrochemical performance of all-solid-state Li-ion batteries. Using nuclear magnetic resonance spectroscopy, Yu et al reported that the electrolyteelectrode Li 6 PS 5 Cl-Li 2 S interface is the dominant factor responsible for the restricted power performance.…”
mentioning
confidence: 99%